Identification of Arx targets unveils new candidates for controlling cortical interneuron migration and differentiation - Friocourt, Gaelle M.; Parnavelas, John G. (Frontiers in Cellular Neuroscience, 2011)
Mutations in the homeobox transcription factor ARX have been found to be responsible for a wide spectrum of disorders extending from phenotypes with severe neuronal migration defects, such as lissencephaly, to mild forms of intellectual disabilities without apparent brain abnormalities, but with associated features of dystonia and epilepsy. Arx expression is mainly restricted to populations of GABA-containing neurons. Studies of the effects of ARX loss of function, either in humans or mutant mice, revealed varying defects, suggesting multiple roles of this gene in brain patterning, neuronal proliferation and migration, cell maturation and differentiation, as well as axonal outgrowth and connectivity. However, to date, little is known about how Arx functions as a transcription factor or which genes it binds and regulates. Recently, we combined chromatin immunoprecipitation and mRNA expression with microarray analysis and identified approximately 1000 gene promoters bound by Arx in transfected neuroblastoma N2a cells and mouse embryonic brain. To narrow the analysis of Arx targets to those most likely to control cortical interneuron migration and/or differentiation, we compare here our data to previously published studies searching for genes enriched or down-regulated in cortical interneurons between E13.5 and E15.5. We thus identified 14 Arx-target genes enriched (Cxcr7, Meis1, Ppap2a, Slc12a5, Ets2, Phlda1, Zif268, Igf1, Lmo3, Sema6, Lgi1, Alk, Tgfb3, Napb) and 5 genes specifically down-regulated (Hmgn3, Lmo1, Ebf3, Rasgef1b and Slit2) in cortical migrating neurons. In this review, we present these genes and discuss how their possible regulation by Arx may lead to the dysfunction of GABAergic neurons, resulting in mental retardation and epilepsy.